Pengelolaan Pembelajaran Berbasis Web pada Mata Pelajaran Pemasaran Online di SMK Negeri 1 Sragen - Susanti, Lina Dwi; Murtiyasa, Budi; Narimo, Sabar (Jurnal VARIDIKA, 2016)
This study aimed to describe about (1) planning to build a web for online marketing learning in SMK N 1 Sragen; (2) the implementation of the limited test marketing web online learning in SMK N 1 Sragen; (3) evaluation of learning Online Marketing at SMK N 1 Sragen. The method in this study using the research and development (research and Development / R & D). Collecting data through observation, interviews, questionnaires (kuesiomer) and documentation. To test the validity of the data using a credibility test (internal validity) and Test transferability (external validity). The conclusion of this study is a web-based learning media on the subjects of online marketing in SMK N 1 Sragen developed through five stages, namely: (1) preliminary stage (2) The design phase of the product. This stage is the design and preparation of instructional media online marketing, (3) the stage of production, (4) Validation validation phase includes the stage of expert assessment of the product of learning media and (5) the pilot phase of the learners feasible to use for learning pemasran online at SMK N 1 Sragen.